A REVIEW OF LAST DEVELOPMENTS IN THIN FILMS PARAMETERS OF DIRECT CURRENT SPUTTERING FOR OPTICAL AND BIOMEDICAL APPLICATIONS - JAWAD, AKRAM JASSIM (Innovare Journal of Medical Sciences, 2021)
Nano thin films and nano coating have been applied in different fields in health care system because of their higher antiviral properties. Additionally, as the world have suffered since December 2019 from Covid-19 situation, different scientists and industrials people have tried to apply nano antiviral films and coatings in our daily life. In this short review, nano thin film coating procedure by DC sputtering technique has been reviewed, investigated, and evaluated by using different materials and device parameters in recent years. This report focuses on device factors that affect the thickness of nano-thin films for optical and optic-electric applications. These parameters including time, temperature, power, pressure, and flow rate of gases. The review provides more understanding meaning of the coating procedure by DC sputtering process.